2016
DOI: 10.1186/s12883-016-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival microcirculatory blood flow is altered but not abolished in brain dead patients: a prospective observational study

Abstract: BackgroundThe conjunctival microcirculation has potential as a window to cerebral perfusion due to related blood supply, close anatomical proximity and easy accessibility for microcirculatory imaging technique, such as sidestream dark field (SDF) imaging. Our study aims to evaluate conjunctival and sublingual microcirculation in brain dead patients and to compare it with healthy volunteers in two diametrically opposed conditions: full stop versus normal arterial blood supply to the brain.MethodsIn a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Moreover, brain rSO 2 correlated well with global cerebral perfusion [25]. Tamosuitis et al found that MFI scores were significantly lower for brain and sublingual mucosa of brain-dead patients compared with those of healthy controls [26].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, brain rSO 2 correlated well with global cerebral perfusion [25]. Tamosuitis et al found that MFI scores were significantly lower for brain and sublingual mucosa of brain-dead patients compared with those of healthy controls [26].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, conjunctival microcirculation can provide insight into pathophysiology of conditions that can alter systemic circulation (Ohtani, 1996; Schaser et al, 2003; Tamosuitis et al, 2016; Yin et al, 2016). Establishing measurement variability is essential for discriminating between true hemodynamic alterations and random fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Application of these imaging modalities has shown conjunctival microvasculopathy and hemodynamic alterations due to systemic diseases such as Alzheimer's disease (Smith et al, 2009), hypertension (To et al, 2013), hypotension (Gaynes et al, 2012), diabetes (Khansari et al, 2017; Cheung et al, 2009; Cheung et al, 2001; Owen et al, 2008; To et al, 2011), and sickle cell disease (Cheung et al, 2002a; Kord Valeshabad et al, 2015; Paton, 1962; Wanek et al, 2013). Furthermore, a recent study showed a significant decrease in conjunctival blood flow, vessel density and non-perfused areas in brain dead subjects as compared to normal controls (Tamosuitis et al, 2016). Moreover, abnormal conjunctival hemodynamics was reported during internal carotid artery surgery (Schaser et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the endothelial dysfunction occurs and inflammatory cytokines are secreted from the endothelial cells resulting in ultimate endothelial detachment. Finally, thrombosis of the vessels occurs . However, knowledge of vascular changes in brain dead patients is very primitive and data accordingly are scarce.…”
Section: Introductionmentioning
confidence: 99%